1989
DOI: 10.1038/clpt.1989.122
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of medication compliance in a drug trial: Limitations of pill counts

Abstract: To assess medication compliance over time, we prospectively performed pill counts among 121 ambulatory hypertensive subjects for less than or equal to 12 months. Prescribed regimens consisted of pinacidil or hydralazine administered four times a day and of secondary drugs administered up to twice daily. Surreptitious pill counts occurred every 1 to 12 weeks. Among a middle-aged subject group that had been selected for high rates of compliance, we observed mean compliance rates that approximated 100%. We noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(85 citation statements)
references
References 0 publications
6
75
1
3
Order By: Relevance
“…Finally, the pill count method is subject to possible errors being made by the person who counts the pills. As reported by others (13), our data show that near-optimal average compliance rates may mask con siderable variability within and between subjects. Since it has been demonstrated that compliance may just as well be poor when an excessive number of tablets seems to have been taken {14), we used the frequency of counts yielding devia tions from the prescribed amount of at least 10% in either direction as one of our outcome measures.…”
Section: Discussionsupporting
confidence: 60%
“…Finally, the pill count method is subject to possible errors being made by the person who counts the pills. As reported by others (13), our data show that near-optimal average compliance rates may mask con siderable variability within and between subjects. Since it has been demonstrated that compliance may just as well be poor when an excessive number of tablets seems to have been taken {14), we used the frequency of counts yielding devia tions from the prescribed amount of at least 10% in either direction as one of our outcome measures.…”
Section: Discussionsupporting
confidence: 60%
“…We compared NPEP regimen completion rates with those of clinic controls, but unmeasured biases limit any conclusion concerning equivalence or superior tolerability. Announced pill counts may result in an overestimation of adherence because social desirability can result in 'pill dumping' before a scheduled visit [32]. However, when used to assess adherence in HIV-positive patients on antiretroviral treatment, pill counts have been shown to correlate with electronic drug monitoring and HIV viral load and provide an objective measure of adherence [33].…”
mentioning
confidence: 99%
“…14 Pill counts, requiring patients to return unused pills at each visit so that the number of missed doses can be calculated, have also been shown to overestimate the number of pills actually taken. 15,16 Patients may throw away missed doses to avoid being viewed as nonadherent. Nonetheless, pill counts are often used as an adjunct to self-report.…”
Section: Indirect Methods Of Measuring Adherencementioning
confidence: 99%